Cylinder Overhaul Restores Dimensional Accuracy and Emission Compliance: Perbaikan Silinder Memulihkan Ketepatan Dimensi dan Kepatuhan Emisi - Fakhrudin; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Multi Purpose Vehicles require proper engine maintenance to sustain operational reliability and emission compliance. Specific Background: Cylinder wear in MPV engines leads to loss compression, reduced power, and inefficient fuel combustion, requiring overhaul procedures involving inspection, oversize machining, component replacement, and emission testing. Knowledge Gap: Quantitative documentation of dimensional changes in cylinder blocks, pistons, and piston ring end gaps before and after overhaul in MPV engines remains limited. Aims: This study aims to analyze the cylinder overhaul process in an MPV engine and evaluate dimensional measurements and exhaust gas emissions after repair. Results: Initial measurements showed cylinder diameter reduction from the 72.00 mm standard to an average of 71.91 mm and piston wear below standard limits. After oversize machining and component replacement, cylinder diameter reached 72.48 mm and piston diameter 72.50 mm, while piston ring gaps returned within standard ranges. Emission testing indicated CO at 0.05%, HC at 25 ppm, and CO2 at 14.7%, meeting regulatory thresholds. Novelty: The study presents integrated dimensional measurement and emission validation within a single overhaul analysis. Implications: The findings provide practical technical guidance for accurate cylinder overhaul procedures in MPV maintenance. Keywords: Cylinder Overhaul, MPV Engine Maintenance, Dimensional Measurement, Piston Ring Clearance, Exhaust Emission Test Key Findings Highlights Pre-repair measurements identified significant wear beyond tolerance limits Post-repair machining achieved conformity with manufacturer specifications Exhaust parameters satisfied regulatory requirements after reassembly